Determination of potential sources of Quercus airborne pollen in Córdoba city (southern Spain) using back-trajectory analysis - Hernández-Ceballos, M. a.; García-Mozo, H.; Adame, J. a.; Domínguez-Vilches, E.; Bolívar, J. P.; De la Morena, B. a.; Pérez-Badía, R.; Galan, C.; la Morena, B a.; Pérez-Badía, R.; Galan, C. (Aerobiologia, 2011)
The northern area of Co´rdoba province (southern Spain) is characterised by a high spatial distribution of Quercus species. In Co´rdoba city, high airborne Quercus pollen counts are detected during spring despite the low presence of Quercus populations in the Guadalquivir Valley, where this city is located. This study sought to clarify and identify the potential origin of the different Quercus peaks detected in this city and chart the possible relationship between Quercus pollen curves and air-mass movements. For this purpose, an integrated study of daily and intra-diurnal Quercus pollen counts and back-trajectory analysis was performed over the March–June period of the years 2006–2008. The application of cluster techniques to back trajectory enabled the identiﬁcation of six different types of air-mass movement. As a function of frequency, two different air-mass groups were identi- ﬁed: the main group comprised Local, Slower Northwest and Mediterranean movements, characterised by higher frequencies; a second group consisting of North, Faster Northwest and Southwest trajectories occurred less frequently over the study period. Although a signiﬁcant correlation was observed between Quercus airborne pollen counts recorded in Co´rdoba city and the inﬂuence of the Mediterranean air-mass movements, the strongest positive correlation was found between North and Northwest air-mass movements and daily Quercus pollen counts. These results would conﬁrm both that the major Quercus pollen sources are located at different distances north of the city and a new pollen source is also located south of the province, beyond the Guadalquivir valley, related to the arrival of Mediterranean air masses. The northern source appears to be linked to regional transport and the southern source to long-range transport.
Keywords: HYSPLIT; Mediterranean; Oak pollen; Synoptic conditions; Transport